Campos do bioma Pampa no contexto de silvicultura: uso da terra, manejo e fatores ambientais como determinantes da vegetação campestre - Torchelsen, Fábio Piccin (2016)
South American Pampa grasslands have been intensely converted into afforestation. While necessity for restoration grows, no information on restoration potential of grasslands after afforestation exists. We evaluated the spontaneous recovery of grasslands with a long history (50 years) of eucalyptus plantation. We sampled grassland vegetation at post-eucalyptus sites (with and without resprouting) ten years after clearclutting and in natural grasslands. Species richness and vegetation cover were higher in reference grassland than in resprout-areas, but did not differ from post-eucalyptus areas. Exotic species cover was significantly higher in areas with afforestation history. In terms of total composition, natural grasslands differed significantly from areas with past plantation use, with some vicinty of grassland types in the ordination diagram. Indicator species analyses revealed considerable differences in typical species as well as functional group composition when comparing the reference grassland to the grassland with history of afforestation. In conclusion, vegetation development led to grassland communities that are still quite distinct from reference sites. Likely, it is the specificity of grassland management, which was not controlled in our study, that determines vegetation trajectories in time. The influence of management for grassland recovery and restoration needs to be addressed in more studies.